A framework for digital preservation of Indigenous knowledge system (IKS) in repositories in South Africa. (16th June 2021) - Balogun, Tolulope; Kalusopa, Trywell
Abstract : Purpose: The purpose of this study is to assess the digital preservation policies and plans for long-term digital preservation in selected repositories in South Africa, with a view to develop a digital preservation framework for the preservation of Indigenous knowledge system (IKS) in South Africa. Design/methodology/approach: Through the multiple case study research design, data was obtained from eight respondents in four Indigenous Knowledge Systems Documentation Centers (IKSDCs) in institutions that are part of the National Recordal Systems (NRS) initiative across four provinces in South Africa using in-depth face-to-face interviews. Data collected was also supplemented with the content analysis of several policy documents in South Africa. Findings: The findings reveal that there are no digital preservation policies in place in the institutions, especially long-term digital preservation for IKS. However, some of the institutions are formulating policies that will include the management of IKS collected in the institutions. This study also reveals that digital curation, policy formulation and disaster preparedness plans to some extent are measures said to be in place for the digital preservation of IKS. Research limitations/implications: This study focuses mainly on the NRS initiative in South Africa. Indigenous Knowledge (IK) related to traditional medicine, traditional plants and food are currently being digitized at the IKSDCs by IK recorders. This study will help in ensuring that the South African Government's effort and investment in digitizing IKS and making them accessible online is not wasted. This study will help mitigate the risk of damage and alteration over time, either deliberately or in error. Originality/value: This study fills a gap in the literature on the digitization and digital preservation of IKS from the context of the NRS project in South Africa. Very few studies have been carried out on the digital preservation of IKS in Africa. This study also proposed a framework for the digital preservation of IKS in South Africa.